The Influence of E-Commerce, Accounting Information Systems, and Entrepreneurship Knowledge on Entrepreneurial Interest - Gabrena Septi Aulia; Sri Trisnaningsih (Golden Ratio of Auditing Research, 2026)
This study aims to analyze the effect of e-commerce, accounting information systems, and entrepreneurial knowledge on entrepreneurial interest in accounting students at Universitas Pembangunan Nasional Veteran Jawa Timur.  The research method used is quantitative, and questionnaires were distributed to 78 respondents from the 2021 student population. The regression analysis results show that the three variables positively and significantly affect entrepreneurial interest, partially and simultaneously. This finding confirms that mastery of digital technology, information systems, and entrepreneurial knowledge is important in encouraging students to start a business. Therefore, integrating technology-based learning and entrepreneurship must be improved in higher education to produce adaptive young entrepreneurs.